TRIAS POLITICA DALAM PERSPEKTIF FIKIH SIYASAH - Wery Gusmansyah (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2017)
According to the concept of the trias politica Montesquieu, in every government there are three kinds of powers, namely the legislative power, the executive power, on matters pertaining to the law of nations; and judicial power on matters that depend on civil law ". According to him, these three types of power must be separate from each other, both about the task (function) and the equipment (organ) that organize it. Basically, the concept of trias politica does not conflict with the jurisprudence of siyasah. The implementation of this power-sharing can be seen in the time of the khulafaurrasyidin. At that time the executive power held by a caliph, the legislative power held by the Council of Shura, and the power of the judiciary held by Qadhi or judge. Then, during the second caliphate of Umar bin Khattab, the division of power between the executive, the legislative, and the judiciary was elaborated by law. At this time, Umar bin Khattab made a law that separates the executive and legislative powers, with the aim that the qadhi as the holder of the judicial power in deciding cases can be free from executive influence